Assessment of the institutional trust level of students in modern Russian society in the context of global cultural and digital transformations - M. A. Tanina; V. V. Bondarenko; V. A. Yudina; O. A. Zyablikova (Вестник университета)
One of the key factors influencing the political development and stability of the Russian Federation (hereinafter referred to as RF, Russia) is trust of citizens in political and social institutions. At the same time, youth is part of the Russian society with which the strategic prospects for progress of the country and vectors of socio-economic transformations are connected. The insufficient degree of confidence in the authorities will hinder effective implementation of societal development processes that also occur in socio-economic and institutional systems. The article presents the questionnaire results of students from Russian universities (N = 780 people) and colleges (N = 780 people) conducted in 2023; educational institutions are located in 41 subjects of the RF in all federal districts. The study revealed a relatively low level of trust of the Russian student youth to various government institutions, while the level of trust in regional authorities is lower than in fede ral ones. This is due to lack of awareness of young people about their activities. Additionally, most of the youth does not undertake a purposeful search and critical analysis of information, does not follow news about the work of authorities. It was also revealed that various network information spaces (social networks, regional digital Internet communities, official websites of government bodies and news portals) have a significant potential to increase institutional trust of students, since they cause the highest level of confidence.